Cardiovascular efficacy and safety of sodium‐glucose co‐transporter‐2 inhibitors and glucagon‐like peptide‐1 receptor agonists: a systematic review and network meta‐analysis. Issue 4 (30th January 2019) - Hussein, H.; Zaccardi, F.; Khunti, K.; Seidu, S.; Davies, M. J.; Gray, L. J.
Abstract: Aims: To compare the cardiovascular efficacy and safety of sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors and glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) in adults with Type 2 diabetes. Methods: Electronic databases were searched from inception to 22 October 2018 for randomized controlled trials designed to assess the cardiovascular efficacy of SGLT2 inhibitors or GLP‐1RAs with regard to a three‐point composite measure of major adverse cardiovascular events (non‐fatal stroke, non‐fatal myocardial infarction and cardiovascular mortality). Cardiovascular and safety data were synthesized using Bayesian network meta‐analyses. Results: Eight trials, including 60 082 participants, were deemed eligible for the network meta‐analysis. Both SGLT2 inhibitors [hazard ratio 0.86 (95% credible interval 0.74, 1.01]) and GLP‐1RAs [hazard ratio 0.88 (95% credible interval 0.78, 0.98)] reduced the three‐point composite measure compared to placebo, with no evidence of differences between them [GLP‐1RAs vs SGLT2 inhibitors: hazard ratio 1.02 (95% credible interval 0.83, 1.23)]. SGLT2 inhibitors reduced risk of hospital admission for heart failure compared to placebo [hazard ratio 0.67 (95% credible interval 0.53, 0.85)] and GLP‐1RAs [hazard ratio 0.71 (95% credible interval 0.53, 0.93)]. No differences were found between the two drug classes in non‐fatal stroke, non‐fatal myocardial infarction, cardiovascular mortality, all‐cause mortality or safety outcomes. Conclusions: SGLT2 inhibitors and GLP‐1RAs reduced the three‐point major adverse cardiovascular event risk compared to placebo, with no differences between them. Compared with GLP‐1RAs and placebo, SGLT2 inhibitors led to a larger reduction in hospital admission for heart failure risk. What's new?: Sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors and glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) are two classes of anti‐hyperglycaemic drugs with additional benefits of reducing cardiovascular risk. Comparisons between SGLT2 inhibitors and GLP‐1RAs in cardiovascular outcome trials have not yet been carried out. In the present analysis, a reduction of cardiovascular risk was observed for SGLT2 inhibitors and GLP‐1RAs compared to placebo in people with Type 2 diabetes, but few differences were observed between the two treatments. SGLT2 inhibitors reduced heart failure risk to a greater extent than GLP‐1RAs and placebo. Results from this study can aid clinicians in selecting suitable anti‐hyperglycaemic therapies for individuals with Type 2 diabetes.